Perancangan Transformator Satu Fasa Dan Tiga Fasa Menggunakan Perangkat Lunak Komputer - Adhitya Franager; Budhi Anto; Dian Yayan Sukma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The transformer is widely used, both in the field of electricity and electronics. Use of the power system allows choosing the appropriate voltage and economical for each purposes. To obtain a good and satisfying design it is necessary to use computer software in design process. The design of single phase and three phase transformer with the help of computer software is intended to replace the conventional process which is done manually so as to improve the efficiency of time and energy. In this research, we use visual basic 6.0 as a program language and the golden ratio (1 : 1,618) is used as the ratio between the width and thickness of the iron coreKeywords: Transformer, Visual Basic 6.0, Golden Ratio